Occurrence of Paraleucilla magna (Porifera: Calcarea) in the Mediterranean Sea - Longo, C.; Mastrototaro, F.; Corriero, G. (Journal of the Marine Biological Association of the United Kingdom, 2007)
The calcareous sponge Paraleucilla magna has been detected at different Mediterranean sites (Taranto, Porto Cesareo, Brindisi and Naples). Its record in well studied areas where several benthic surveys have previously been carried out suggests a recent introduction of the species into the Mediterranean Sea. Until now this sponge has only been recorded from the Brazilian coast. It shows different morphologies, varying from tubular to an irregular massive shape with several folds occurring on its surface. The colour is white-cream. The surface is smooth. The consistency is friable. The oscula are 10–20 mm in diameter and located at the top of tubular protrusions. The skeleton consists of cortical and subatrial triactines and tetractines, together with atrial triactines, differently distributed in the sponge body. Paraleucilla magna is abundant in eutrophic environments, where seasonally it may reach very high frequency values and large dimensions. It is resistant to pollution, but it is also able to live in clean waters. The inclusion of this species among Mediterranean alien invasive species is suggested.